Guidelines for nurse practitioners in gynecologic settings - Hawkins, Joellen Watson (Springer Pub., 2012)
This textbook provides the busy clinician with a 'one stop' comprehensive guide to women's health that includes essential components of the history, diagnostic workup, treatment, and management guidelines for most common health issues and problems.